Brazilian University Ecomuseums: Challenges and Potentialities (Cadernos de Sociomuseologia, 2023)
The present article aims to analyze the Brazilian University Ecomuseums, their actions, projects, challenges and potential when being considered a hybrid museum, being simultaneously an Ecomuseum and a University Museum. We highlight the relationship between theory and practice of an Ecomuseum, prioritizing the integrated action of communities and their heritage and territories. And the university pillars in teaching, research and extension and how an Ecomuseum inserted in this scope enhances its mission and scientific and community values. This work makes use of the theoretical-conceptual foundation of this type of museum, involving the notions of territory, community, scientific and integral heritage, and the challenges and potential of a university Ecomuseum. In the interaction and integration of knowledge, subjects and interests, investment is made in the transforming power of knowledge and its own forms of production, enabling the realization of an “ecology of knowledge”. The ecomuseum becomes a field of multiple research, of different research groups, undergraduate and graduate courses, covering as an object of study and heritage the territory, with its fauna, flora, rivers, sea, anthropic processes, stories and memories of the local population.Key words: Ecomuseum, University, Hibrid Museum, Community, Territory.